The development of the American College Health Association-National College Health Assessment III: An improved tool to assess and enhance the health and well-being of college students. Issue 6 (24th August 2022) - Lederer, Alyssa M.; Hoban, Mary T.
Abstract: This article describes the development of the American College Health Association-National College Health Assessment III (ACHA-NCHA III), a widely used comprehensive survey that assesses college students' health behaviors and outcomes at the institutional and national levels. Only the second major revision since the ACHA-NCHA was established in 2000, the ACHA-NCHA III launched in Fall of 2019. Background on the purpose and history of the ACHA-NCHA will first be provided. Then the systematic steps taken to create a new and enhanced version of the survey will be recounted. An overview of the final ACHA-NCHA III instrument will be given, and future directions for the survey post-implementation will be discussed.